The Evolutionary Theory of Jealousy: A Cross-Cultural Test - Mellgren, Roger L. (Array, 2006)
The two alternative forced choice method was used to assess how upset males and females were in the sexual or emotional infidelity of their mate with either a same sex person (homosexual relationship) or an opposite sex person (heterosexual relationship). A checklist of emotions was also given to the subjects to assess in more detail their feelings about the infidelities. In both the US and Croatia females showed a strong tendency to be upset by the emotional infidelity in the heterosexual case, but a complete reversal to the sexual infidelity in the homosexual case. Males were more upset by the sexual infidelity than females in the heterosexual case, but less upset by the sexual infidelity than the females in the homosexual case. Self reported emotions revealed anger, disgust and sadness to differentiate the feelings of the subjects to the different situations.